Pamięć uwikłana w próżnię. Shoah i różne wymiary nie-bycia miejsc w Berlinie - Posłuszny, Łukasz (Wydawnictwo Uniwersytetu Gdańskiego, 2014)
Landscape of Berlin was shaped significantly by numerous accidental and planed events. Air raids during the Second World War, the construction and demolition of the Berlin Wall created in the aftermath many physically empty spaces and voids in the city structure. However not only military operations, urbanists and architects’ actions shape city environment. Artistic and social activities, individual and social memory can also highlight the ambiguous nature of places by restoring their old dimensions or playing with their stable contemporary meaning. The text devotes attention to such architectural projects in Berlin, which work with memory and representation of the holocaust by abandoning simply understood ideas of space and place used in traditional monuments. The text focuses on the play with emptiness that constitutes, reduces and broadens the understanding of an idea of the monument and redefines concept of a place. This paper addresses the projects of D. Libeskind Jewish Museum, C. Boltanski Missing House, M. Ullman Book Burning Memorial, Z. Hecker, M. Ullman, and E. Weizman Page Memorial, and G. Demnig Stumblingblocks.
Keywords: Pamięć; holokaust; Berlin; miejsca pamięci; nie-miejsca; pomnik; upamiętnianie; Peter Eisenman; Daniel Libeskind; Stolpersteine; antypomnik